Revalidation of morphological characteristics and multiplex PCR for the identification of three congener invasive Liriomyza species (Diptera: Agromyzidae) in China - Chang,Ya-Wen; Chen,Jing-Yun; Zheng,Si-Zhu; Gao,Yuan; Chen,Yunfang; Deng,Yanfeng; Du,Yu-Zhou (PeerJ, 2020)
Due to varietal differences, diminutive size, and similar morphological characters, it is difficult to classify and identify Liriomyza spp., a genus comprised of economically-important, highly-polyphagous insect pests. In this study, we reconfirmed the morphological characteristics of three closely-related invasive leafminers, L. trifolii, L. sativae, and L. huidobrensis. Morphological results showed that characteristics imparted by the male genitalia were the most reliable morphological features for identification. The colors exhibited by vertical setae were variable among species, and the ratio of the length of the ultimate section of vein CuA1 divided by penultimate section also varied within species. Although the patterns of abdominal tergites were diverse among Liriomyza spp., L. trifolii exhibited a unique pattern with a yellow patch at the 5th black visible tergite; this pattern can be profiled as a prominent characteristic for morphological identification. In order to identify the three Liriomyza spp. quickly and accurately, we developed an improved molecular identification method using multiplex PCR based on the gene encoding mitochondrial cytochrome oxidase I (COI); this method enabled direct identification based on the size of amplified products. The results of this study provide a valuable reference for the identification of Liriomyza spp., which will ultimately improve our ability to control individual species.
Keywords: Liriomyza; Morphological characteristics; Abdominal tergites; Multiplex PCR; Species identification; COI